Medical Aid in Dying and Dementia Directives - Pope, Thaddeus (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
Although Canada recently expanded access to medical assistance in dying, intolerably suffering Canadians with dementia still face seven obstacles to qualify for MAID. Advance directives for VSED are an important, yet under-appreciated, alternative.